Secondary Trimester Pregnancy in Systemic Lupus Erythematosus Patients withPneumonia: A Case Report - Reza Mahardika (Indonesian Rheumatology Associantion, 2023)
Background. Systemic lupus erythematosus (SLE) is an autoimmunedisease that can attack multiple organs and has a high prevalence in women.Due to its treatment and resulting pathological conditions, SLE makes thepatient susceptible to infections. Furthermore, physiological changes in thebody that occur during pregnancy renders pregnant women with SLEvulnerable to disease exacerbation. Therefore, the management of suchcases necessitates the evaluation and intervention of a multidisciplinarymedical team. Case Presentation. We present the case of a female patientin her second trimester of pregnancy who complained of shortness of breath.The patient has a history of SLE diagnosed five years ago. Within 7 days oftreatment, the patient experienced an improvement in symptoms. Conclusion. This is a rare case, and we report on the outcomes of treatmentand our limitations to ensure better future treatment for pregnant womenwith SLE to prevent maternal and fetal death.